Clinical manifestations of polymorbidity in patients with vitligo - M. M. Tlish; E. B. Popovskay; T. G. Kuznetsova; N. L. Sycheva; J. Yu. Naatyzh (Лечащий Врач)
In the article, vitiligo appears as a chronic multifactorial disease of the skin of unclear etiology from the group of dyschromias with completely different mechanisms of its pathogenesis and levels of malignant melanin formation in the skin. The authors provide their own clinical observations of patients with vitiligo in combination with psoriasis, atopic dermatitis, rosacea.